2017
DOI: 10.2298/ntrp1704334d
|View full text |Cite
|
Sign up to set email alerts
|

Natural and artificial radioactivity in some protected areas of south east Europe

Abstract: and En vi ron men tal Pro tec tion, Uni ver sity Un ion-Nikola Tesla, Bel grade, Ser bia 2 In no va tion Cen tre, Fac ulty of Me chan i cal En gi neer ing, Uni ver sity of Bel grade, Bel grade, Ser bia 3 De part ment of Ra di a tion and En vi ron men tal Pro tec tion, Vin~a In sti tute of Nu clear Sci ences, Uni ver sity of Bel grade, Bel grade, Ser bia 4 Min ing In sti tute, L.t.d., Bel grade, Ser bia Sci en tific pa per

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…It could be considered in terms of features of localities: this occurred in coniferous forests (mosses in pine and spruce forests more readily uptake radionuclides than oak forests), and it could be related with acidic conifer needles, its retaining the soil moisture and making different substrate. Džoljić et al (2017) reported very low TF Cs for spruce needles (range from not detected to 0.02), which could confirm washing out effect and deposition in substrate by precipitation. The most important way of 137 Cs deposition in moss tissue is possibility that 137 Cs remains on the surface, which influences soil resuspension and transport to mosses (Ioannidou & Papastefanou, 2006, Krmar et al, 2018; also, 137 Cs can be transported during growing period from older sections to newer sections of moss tissue (Krmar et al, 2018).…”
Section: Resultsmentioning
confidence: 83%
“…It could be considered in terms of features of localities: this occurred in coniferous forests (mosses in pine and spruce forests more readily uptake radionuclides than oak forests), and it could be related with acidic conifer needles, its retaining the soil moisture and making different substrate. Džoljić et al (2017) reported very low TF Cs for spruce needles (range from not detected to 0.02), which could confirm washing out effect and deposition in substrate by precipitation. The most important way of 137 Cs deposition in moss tissue is possibility that 137 Cs remains on the surface, which influences soil resuspension and transport to mosses (Ioannidou & Papastefanou, 2006, Krmar et al, 2018; also, 137 Cs can be transported during growing period from older sections to newer sections of moss tissue (Krmar et al, 2018).…”
Section: Resultsmentioning
confidence: 83%
“…In addition to the natural radionuclides, the artificial 137 Cs was detected in the soil, grass, spruce, cow milk and moss samples from Mt. Kopaonik (Mitrović et al, 2016;Džoljić et al, 2017). In the soil, the lowest activity concentration of 137 Cs was recorded in the area of Pančićev vrh, and the maximum in Jošanjička banja (Table 5).…”
Section: The Mountain Of Kopaonikmentioning
confidence: 99%
“…The results of gamma spectrometric determination of radionuclides in the soil collected on nine locations at Mt. Kopaonik during 2013-2016 (Mitrović et al, 2014(Mitrović et al, , 2016Džoljić et al, 2017) and radiation hazard parameters are presented in Tables 5 and 6, respectively.…”
Section: The Mountain Of Kopaonikmentioning
confidence: 99%
“…Also, tour ists of ten visit this area out of cu ri os ity, ig nor ing that this is a re stricted area due to in ad e quate se cu rity mea sures in past de cades. Like wise, ac tiv i ties typ i cal for this re gion, es pe cially in the tour ist sea son, e. g. dairy prod ucts or herbal man u fac tur ing and sales, might trans fer the con tam i na tion [9,10].…”
Section: Introductionmentioning
confidence: 99%